Spectroscopic diagnostic of isolated dense plasma generated through laser driven gold hohlraum radiation. Issue 19 (January 2020) - Ren, J; Zhao, Y; Deng, Z; Qi, W; Cheng, R; Wang, X; Liu, W; Ma, B; Yin, S; Chen, B; Feng, J; Wang, S; et al.
Synopsis: Through indirectly heating a TAC foam with ns laser driven gold hohlraum radiation, isolated, highly homogeneous and long-living dense ionized matter was generated in laboratory. This provide a fantastic sample for investigation of dense plasma science and technology. The emission spectra of the plasma with time, spatial and spectral resolution were measured with various techniques. The temperature and electron density are precisely diagnosed on the basis of the spectra.